Perturbation of Auxin Homeostasis and Signaling by PINOID Overexpression Induces Stress Responses in Arabidopsis - Saini, Kumud; AbdElgawad, Hamada; Markakis, Marios N.; Schoenaers, Sébastjen; Asard, Han; Prinsen, Els; Beemster, Gerrit T. S.; Vissenberg, Kris (Frontiers in Plant Science, 2017)
Under normal or stress conditions plant growth requires a complex interplay between phytohormones and reactive oxygen species (ROS). However, details of the nature of this crosstalk remain elusive. Here we demonstrate that PINOID (PID), a serine threonine kinase of the AGC kinase family, perturbs auxin homeostasis, which in turn modulates rosette growth and induces stress responses in Arabidopsis plants. Arabidopsis mutants and transgenic plants with altered PID expression were used to study the effect on auxin levels and stress-related responses. In the leaves of plants with ectopic PID expression an accumulation of auxin, oxidative burst and disruption of hormonal balance was apparent. Furthermore, PID overexpression led to the accumulation of antioxidant metabolites, while pid knockout mutants showed only moderate changes in stress-related metabolites. These physiological changes in the plants overexpressing PID modulated their response towards external drought and osmotic stress treatments when compared to the wild type. Based on the morphological, transcriptome and metabolite results, we propose that perturbations in the auxin hormone levels caused by PID overexpression, along with other hormones and ROS downstream, cause antioxidant accumulation, modify growth and stress responses in Arabidopsis. Our data provide further proof for a strong correlation between auxin and stress biology.